Two‐Step Magnetic‐Pulling Chemical Vapor Deposition Growth of CdS1−xSex Lateral Nanoribbon Heterostructures for High‐Performance Photodetectors. Issue 3 (20th January 2023) - Shen, Xia; Lv, Qihang; Yang, Qian; Fan, Jie; Song, Xiaohang; Guo, Pengfei; Li, Pu; Ho, Johnny C.; Yu, Kin Man
Abstract : Bandgap integration in a single semiconductor nanostructure is an important task for their applications in photonics and photoelectronics. Herein a two‐step growth of CdS x Se1− x alloy nanoribbon heterostructures along the lateral direction by an improved two‐step magnetic‐pulling chemical vapor deposition (CVD) method is reported. Microstructural characterizations further demonstrate that these ribbons are formed by two separate components along the lateral direction of the nanoribbons, including CdS0.76 Se0.24 at the central region and CdS0.44 Se0.56 at both lateral sides, respectively. Under a laser excitation, photoluminescence spectrum and 2D emission mapping at the junctions show two different emission bands at 555 and 603 nm, which show agreement with the structural characterization results. More importantly, under 355 nm laser illumination, room‐temperature dual‐wavelength lasing with peak center at 542.3 and 605.2 nm is realized using these sandwich‐like nanoribbons. Additionally, photodetectors based on these achieved nanoribbons are fulfilled with great performance of high responsivity (2.4 × 10 4 A W −1 ), high external quantum efficiency of 2.9 × 10 5 %, fast response speed (rise ≈25 ms, decay ≈21 ms), and high I on / I off ratio (10 6 ). These structures may offer an interesting system for exploring new applications in multifunctional nanophotonic and optoelectronic devices, such as high‐performance detectors, miniature tunable lasers, and high‐density color displays. Abstract : Herein, a high‐quality lateral nanoribbon heterostructure with an abrupt interface using a two‐step magnetic‐pulling chemical vapor deposition approach is reported. Room‐temperature dual‐wavelength lasing and high‐performance photodetectors are demonstrated based on these unique nanostructures.